1995
DOI: 10.1016/0014-5793(95)01013-5
|View full text |Cite
|
Sign up to set email alerts
|

The block of the expressed L‐type calcium channel is modulated by the β3 subunit

Abstract: The a~c subunit of the L-type calcium channel was stable, expressed alone or in combination with the/33 subunit in Chinese hamster ovary cells. The /33 subunit enhanced significantly the inactivation of barium currents indicating that both subunits interacted with each other. The /]3 subunit decreased significantly the half-maximal inhibitory concentration of the calcium channel blockers (-)-gallopamil and verapamil, but did not affect significantly the block caused by isradipine and mibefradil at the holding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…13,14 Also, the peak ICa,L density is known to be increased by co-expression of the (Cacnb) auxiliary subunit, [14][15][16] although there have been contro- versial results reported for 3 (Cacnb3). 17 On the basis of these reports, the present electrophysiological observations would be explained simply by the decreased amount of the main subunit 1C (Cacna1c) (Cav1.2) in the atrium being compensated for by the increased auxiliary subunit 2 (Cacna2d), leading to similar ICa,L density in the atrium and the ventricle. In this consideration, the voltage dependence of inactivation and activation of ICa,L should show a hyperpolarized shift in the atrium through the increased 2 (Cacna2d), contradictory to our observation of a depolarized shift.…”
Section: Discussionmentioning
confidence: 54%
“…13,14 Also, the peak ICa,L density is known to be increased by co-expression of the (Cacnb) auxiliary subunit, [14][15][16] although there have been contro- versial results reported for 3 (Cacnb3). 17 On the basis of these reports, the present electrophysiological observations would be explained simply by the decreased amount of the main subunit 1C (Cacna1c) (Cav1.2) in the atrium being compensated for by the increased auxiliary subunit 2 (Cacna2d), leading to similar ICa,L density in the atrium and the ventricle. In this consideration, the voltage dependence of inactivation and activation of ICa,L should show a hyperpolarized shift in the atrium through the increased 2 (Cacna2d), contradictory to our observation of a depolarized shift.…”
Section: Discussionmentioning
confidence: 54%
“…Faster inactivating Ca 2ϩ currents were found to be more efficiently blocked by PAA than more slowly inactivating Ba 2ϩ currents in cardiomyocytes (2). Heterologously expressed Ltype Ca 2ϩ channels are blocked to a larger extent by PAA when ␤ 3 -subunits, which accelerate current inactivation, are coexpressed with ␣ 1C (29).…”
Section: Resultsmentioning
confidence: 99%
“…First evidence for ␤-subunit-dependent PAA sensitivity was reported by Lacinova et al, 25 who observed a higher sensitivity of Ca v 1.2 for (-)gallopamil and verapamil when the ␣ 1 1.2-subunit was coexpressed together with the ␤ 3 -subunit compared with cells transfected solely with ␣ 1 1.2. We have later demonstrated that the PAA sensitivity of a mutant ␣ 1 2.1 construct is determined by ␤-subunitdependent inactivation properties (␣ 1A-PAA ).…”
Section: ␤-Subunit Composition Of Ca V 12 Affects Voltage-dependent mentioning
confidence: 89%